Some Heteroskedasticity Consistent Covariance Matrix Estimators with Improved Finite Sample Properties - James G. MacKinnon; Halbert White (Queen's University, Department of Economics, 1983)
We examine several modified versions of the heteroskedasticity-consistent covariance matrix estimator of Hinkley and White. On the basis of sampling experiments which compare the performance of quasi t statistics, we find that one estimator, based on the jackknife, performs better in small samples than the rest. We also examine finite-sample properties using modified critical values based on Edgeworth approximations, as proposed by Rothenberg. In addition, we compare the power of several tests for heteroskedasticity and find that it may be wise to employ the jackknife heteroskedasticity-consistent covariance matrix even in the absence of detected heteroskedasticity.
Keywords: C10; C12; 330; Jackknife; Heteroskedasticity; HCCME; Edgeworth approximations